The theory of glottagenesis in publicistic discourse by Panas Myrnyi and Oles Honchar (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The paper clarified the problem of the origin of the language in general and the history of the Ukrainian language on the basis of the Slavonic language in particular according to the publicistic version of Panas Myrnyi and Oles Honchar. The author determined common and different issues of the glottagenesis theory suggested by these two masters of artistic expressions.
Keywords: glottagenesis; the Ukrainian language; the common Slavonic language; the common East-Slavonic language; publicistic discourse; Panas Mirnyi; Oles Honchar